Coordination of cell division and chromosome segregation by iron and a sRNA in Escherichia coli - Ng Kwan Lim, Evelyne; Grüll, Marc; Larabi, Nadia; Lalaouna, David; Massé, Eric (Frontiers in Microbiology, 2024)
Iron is a vital metal ion frequently present as a cofactor in metabolic enzymes involved in central carbon metabolism, respiratory chain, and DNA synthesis. Notably, iron starvation was previously shown to inhibit cell division, although the mechanism underlying this observation remained obscure. In bacteria, the sRNA RyhB has been intensively characterized to regulate genes involved in iron metabolism during iron starvation. While using the screening tool MAPS for new RyhB targets, we found that the mRNA zapB, a factor coordinating chromosome segregation and cell division (cytokinesis), was significantly enriched in association with RyhB. To confirm the interaction between RyhB and zapB mRNA, we conducted both in vitro and in vivo experiments, which showed that RyhB represses zapB translation by binding at two distinct sites. Microscopy and flow cytometry assays revealed that, in the absence of RyhB, cells become shorter and display impaired chromosome segregation during iron starvation. We hypothesized that RyhB might suppress ZapB expression and reduce cell division during iron starvation. Moreover, we observed that deleting zapB gene completely rescued the slow growth phenotype observed in ryhB mutant during strict iron starvation. Altogether, these results suggest that during growth in the absence of iron, RyhB sRNA downregulates zapB mRNA, which leads to longer cells containing extra chromosomes, potentially to optimize survival. Thus, the RyhB-zapB interaction demonstrates intricate regulatory mechanisms between cell division and chromosome segregation depending on iron availability in E. coli.